Toward the development of GE11-based radioligands for imaging of epidermal growth factor receptor-positive tumors - Judmann, Benedikt; Braun, Diana; Schirrmacher, Ralf; Wängler, Björn; Fricker, Gert; Wängler, Carmen (ACS omega, 2022)
The epidermal growth factor receptor (EGFR) is closely associated with tumor development and progression and thus an important target structure for imaging and therapy of various tumors. As a result of its important role in malignancies of various origins and the fact that antibody-based compounds targeting the EGFR have significant drawbacks in terms of in vivo pharmacokinetics, several attempts have been made within the last five years to develop peptide-based EGFR-specific radioligands based on the GE11 scaffold. However, none of these approaches have shown convincing results so far, which has been proposed to be attributed to different potential challenges associated with the GE11 lead structure: first, an aggregation of radiolabeled peptides, which might prevent their interaction with their target receptor, or second, a relatively low affinity of monomeric GE11, necessitating its conversion into a multimeric or polymeric form to achieve adequate EGFR-targeting properties. In the present work, we investigated if these aforementioned points are indeed critical and if the EGFR-targeting ability of GE11 can be improved by choosing an appropriate hydrophilic molecular design or a peptide multimer system to obtain a promising radiopeptide for the visualization of EGFR-overexpressing malignancies by positron emission tomography (PET). For this purpose, we developed several monovalent 68Ga-labeled GE11-based agents, a peptide homodimer and a homotetramer to overcome the challenges associated with GE11. The developed ligands were successfully labeled with 68Ga3+ in high radiochemical yields of ≥97% and molar activities of 41-104 GBq/μmol. The resulting radiotracers presented logD(7.4) values between −2.17 ± 0.21 and −3.79 ± 0.04 as well as a good stability in human serum with serum half-lives of 112 to 217 min for the monovalent radiopeptides and 84 and 62 min for the GE11 homodimer and homotetramer, respectively. In the following in vitro studies, none of the 68Ga-labeled radiopeptides demonstrated a considerable EGF receptor-specific uptake in EGFR-positive A431 cells. Moreover, none of the agents was able to displace [125I]I-EGF from the EGFR in competitive displacement assays in the same cell line in concentrations of up to 1 mM, whereas the endogenous receptor ligand hEGF demonstrated a high affinity of 15.2 ± 3.3 nM. These results indicate that it is not the aggregation of the GE11 sequence that seems to be the factor limiting the usefulness of the peptide as basis for radiotracer design but the limited affinity of monovalent and small homomultivalent GE11-based radiotracers to the EGFR. This highlights that the development of small-molecule GE11-based radioligands is not promising.
Gesehen am 23.10.2023